Exploring man-made hazards in our communities: a toxic tour of Kansas - Ashlock, Marcus; Gordon, Joye; Lavergne, Christopher (My University, 2010)
Although we live in a world of frequent, nature-related disasters such as tornados in the Midwest, hurricanes along the eastern coast and earthquakes among the major fault lines in the west, many disasters experienced by the public are man-made. Whether city planners allow residential building permits for flood planes or chemical plants to be erected to boost a local economy, many citizens may feel the adverse effect of this progress when disaster strikes. The U.S. constitution mandates an equality among the population, but sociologists such as Tierney (1999) state “risks are imposed unequally in society, and frequently those most exposed are least able to cope with risk” (p. 231). This presentation showcases a 2008 Tilford Multicultural Grant funded project, an interdisciplinary collaboration of a combined experiential learning module in three (3) courses within two university departments. The Department of Communications in the College of Agriculture and the A.Q. Miller School of Journalism & Mass Communication in the College of Arts & Sciences partnered together to provide a field trip/direct experience opportunity for students, enrolling in AGCOM 420 – Crisis Communications, AGCOM/MC 712 – Environmental Communication and MC 740 – Risk Communication, to see the effects of man-made hazards and disaster on marginalized Kansan populations. The overall course objective is to expose students to the concepts and best practices of risk, crisis, and environmental communications. Through the proposed experiential module, the students were lead on two separate field trips in the spring semester of 2008 to experience the effects of 100 year-old mining techniques in the rural town of Galena, KS, and to tour the Jefferies Energy plant, a coal-fired energy production facility.
Keywords: Nature-related disasters; Risk; Crisis; Environmental communications